THE BIBLICAL INSERTION IN THE JAVANESE QURANIC EXEGESIS: Textual and Contextual Analysis of Tafsir Soerat Wal-’Asri by Siti Chayati, Surakarta (State Islamic University (UIN) of Sunan Ampel Surabaya, 2022)
This study examines the insertion of Biblical sources as references in Tafsir Soerat Wal-’Asri by Siti Chayati, a Javanese Quranic exegete who interprets chapter 103 (al-Asr) of the Quran in Javanese using Javanese Script. The Chayati’s work using some Biblical verses of Barnabas, Matthew, and John as its references, is unique and thought-provoking to understand the motives and its historical background. This study finds that the use of Bible verses in her work was aimed to strengthen her claims on the truth of Islamic teachings against the missionary activities of the Dutch in Java. At the beginning of the 20th century, they attempted to weaken the Islamic community by conducting the Zending movement and establishing Seminary Christian Schools in several regencies in Java. Therefore, debates on religious concepts had become a central issue to win the heart of the traditional Javanese society. The tensions between Christian missionaries and Muslim preachers in that era turned out to be significant factors influencing the insertion of Biblical references in the work of Chayati’s Quranic exegesis.